Pengaruh Media Sosial, Word Of Mouth Dan Kualitas Pelayanan Terhadap Keputusan Berkunjung Wisatawan Muslim Di Wisata Susur Sungai Mahakam - Mainata, Dedy; Ramadhan, Wahid Nur; Parlina, Tika (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The growing interest in Samarinda among tourists, fueled by easily accessible information and transportation, is the driving force behind this study. The preservation of the city's environment and cultural legacy becomes imperative with the inflow of tourists. Sustainable growth requires cooperation between the community and the government. The study intends to evaluate how Muslim tourists using the Mahakam situs toto River Cruise Tour make judgments based on social media, word-of-mouth, and service quality. Through the use of descriptive quantitative research, information is gathered from 100 Muslim visitors who were purposefully sampled using questionnaires. Results show that word-of-mouth does not greatly affect decisions, but social media does. Service quality has a big impact on where people choose to come. Concurrently, these factors contribute to 92.2% of the decision-making process, indicating their critical function in determining Samarinda's tourism environment.